Uji Aktivitas Antibakteri dari Kombinasi Ekstrak Etanol Daun Bidara (Ziziphus Mauritiana L.) dan Daun Kelor (Moringa Oleifera L.) pada Bakteri Propionibacterium Acnes - Rizkyana, Elsie (Innovative: Journal Of Social Science Research, 2024)
Acne is one of the common skin diseases in society. Bidara leaves and Moringa leaves are traditional plants whose content can potentially be an alternative treatment for acne problems caused by Propionibacterium acnes bacteria. This study aims to 1). To determine what types of secondary metabolites are owned by each bidara and moringa leaf extract that act as antibacterials. 2). To determine the concentration that has the greatest antibacterial activity from the combination of ethanol extracts of bidara and moringa leaves on the growth of Propionibacterium acnes. Method: This research is an Experimental Laboratory study with a post-test only control group design. Extraction of bidara and moringa leaves was carried out by maceration using 96% Ethanol solvent and concentrated until a thick extract was obtained, then a combination of both was carried out with concentrations of 10%, 20%, 30%, 40% and 50%. The clear zone results obtained will be calculated for their average value and their antibacterial activity classified according to the Greenwood standard. Results: The combination of bidara and moringa leaf extracts at concentrations of 10%, 20%, and 30% showed the category of "No" antibacterial activity, while at concentrations of 40% and 50% showed the category of "Weak" as an antibacterial, but all concentrations did not exceed the antibacterial activity value of the clindamycin compound. Conclusion: 1). Each extract of bidara leaves (Ziziphus mauritiana L.) and moringa leaves (Moringa oleifera L.) has secondary metabolites that can act as antibacterial. 2). The combination of ethanol extract of bidara leaves (Ziziphus mauritiana L.) and moringa leaves (Moringa oleifera L.) with concentrations of 40% and 50% has greater antibacterial activity with the category "Weak" compared to concentrations of 10%, 20% and 30% with the category "None". Keywords: Ethanol Extract, Bidara Leaves (Ziziphus mauritiana L.), Moringa Leaves (Moringa oleifera L.), Combination, Antibacterial, Propionibacteria acnes